2015
DOI: 10.6113/jpe.2015.15.2.544
|View full text |Cite
|
Sign up to set email alerts
|

Steady-State Analysis of ZVS and NON-ZVS Full-Bridge Inverters with Asymmetrical Control for Induction Heating Applications

Abstract: This paper presents a steady-state operation analysis of full-bridge series-resonant inverters focusing on the distorted load current due to low-quality-factor resonant circuits in induction heating and other applications. The regions of operation based on the zero-voltage switching (ZVS) and non-zero-voltage switching (NON-ZVS) operations of the asymmetrical voltage-cancellation control technique are identified. The effects of a distorted load current under a wide range of output powers are also analyzed for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…To simplify the analysis, the parasitic inductance and capacitance are neglected. The magnitude of the impedance Ẑ eq of the series resonant circuit and the impedance phase angle of harmonic components are found as [17], Fig. 4.…”
Section: A Output Power Controlmentioning
confidence: 98%
See 1 more Smart Citation
“…To simplify the analysis, the parasitic inductance and capacitance are neglected. The magnitude of the impedance Ẑ eq of the series resonant circuit and the impedance phase angle of harmonic components are found as [17], Fig. 4.…”
Section: A Output Power Controlmentioning
confidence: 98%
“…For domestic low-cost vessels, the quality factor value is even lower due to a high damping factor value. The output current is unavoidably distorted and may result in hard-switching conditions during a switching transition at the end of the positive cycle, resulting in non-zero-voltage switching (NON-ZVS) [17]. This means that the switching frequency is required to be much higher than the resonant frequency for ZVS operation.…”
Section: Introductionmentioning
confidence: 99%
“…Two types of inverters are installed into high frequency induction heaters: voltage source and current source. In the past, series and parallel resonant inverter circuits were used in conjunction with half-bridge and full-bridge to reduce switching loss and increase circuit efficiency [7][8][9][10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…A converter structure with proven application in induction heating, giving high power density and the ability to operate with soft-switching, is the full-bridge circuit with a parallel or series resonant tank, based on different modulation techniques, such as Phase-Shift Modulation (PSM), Pulse-Frequency Modulation (PFM), Pulse-Density Modulation (PDM) and Asymmetrical Duty-Cycle (ADC) [25][26][27][28][29][30][31]. These types of modulation offer flexible control over the wide range of output powers [25].…”
Section: Introductionmentioning
confidence: 99%
“…These inverters applied for induction heating can have a good match with a Power Factor Correction (PFC) stage [26]. An additional characteristic of the PSM is the ability of the ZVS to be achieved for the required power range under regulation with variable switching frequency [27]. It has been shown that the use of variable switching has a better efficiency than a fixed switching frequency.…”
Section: Introductionmentioning
confidence: 99%